2018
DOI: 10.1186/s40001-018-0324-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anticoagulation and vasoactive medication on regained radial artery patency after catheterization: a case–control study

Abstract: BackgroundRadial artery access is the primary approach for coronary interventions due to higher safety profile in comparison to femoral access. Radial artery occlusion (RAO) is the main complication of transradial catheterization that can lead to severe symptoms and a permanent artery occlusion. The incidence of RAO after transradial access ranges from 5 to 38% and data regarding treatment is scarce. Whether anticoagulation and vasoactive medication provides an additional benefit in recovery of radial artery p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In addition, novel oral anticoagulants have been approved for venous thromboembolism therapy, though the precise duration of treatment remains debatable. Although a three‐month course of novel oral anticoagulation has been suggested for venous thromboembolism, and up to a 90‐day course of these medications has been trialed anecdotally to treat post‐cardiac catheterization RAO, 15 in this case series of RAO, a 30 day course of apixaban demonstrated efficacy in our experience.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In addition, novel oral anticoagulants have been approved for venous thromboembolism therapy, though the precise duration of treatment remains debatable. Although a three‐month course of novel oral anticoagulation has been suggested for venous thromboembolism, and up to a 90‐day course of these medications has been trialed anecdotally to treat post‐cardiac catheterization RAO, 15 in this case series of RAO, a 30 day course of apixaban demonstrated efficacy in our experience.…”
Section: Discussionmentioning
confidence: 69%
“…There has been limited investigation into the potential impact of novel oral anticoagulants in the treatment of RAO. In subgroup analysis of one study, there were a total of 17 cases of RAO treated with anticoagulation, either with low‐molecular‐weight heparin (10 cases), apixaban (one case), or rivaroxaban (six cases) 15 . The conclusions suggest that anticoagulation is effective in improving the patency rates following RAO, but there is no delineation of specifically which anticoagulation strategies were effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study addressed the treatment of symptomatic RAO and found that low molecular heparin may lead to partial or complete reopening in almost 80% within 4 weeks of treatment [8]. In another study, 15 patients with asymptomatic RAO were treated and a similar percentage of patients who continued treatment for more than 4 weeks regained patency [5].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, time-limited empirical medical regimens are used in order to restore patency and perfusion. A recent study by our team has investigated the benefits of anticoagulation in a small prospective study [5].…”
Section: Introductionmentioning
confidence: 99%